2017
DOI: 10.1530/eje-16-0812
|View full text |Cite
|
Sign up to set email alerts
|

The neuroendocrine sequelae of paediatric craniopharyngioma: a 40-year meta-data analysis of 185 cases from three UK centres

Abstract: The shift towards more conservative surgery has reduced the prevalence of hormone deficiencies, including diabetes insipidus, which can be life threatening. However, it has not been associated with reduced hypothalamic and visual morbidities, which remain a significant challenge. More effective targeted therapies are necessary to improve outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 39 publications
5
34
1
Order By: Relevance
“…Many published reports on long-term follow-up after childhood-onset CP are focused on survival rates and lack information on specific sequelae (22,25,26,27,30). However, QoS is frequently impaired in the pediatric age group due to treatment and/or disease-associated factors such as HI, neuropsychological (31,32) and neuroendocrine deficits (16,21,33,34,35,36,37,38,39,40,41,42) including GH deficiency being the most frequent pituitary deficiency (54-100%) (1,37,39). Our study is the first report in the literature, which analyzed not only long-term survival but also psychosocial status and QoS with special regard to timing and duration of GH substitution therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many published reports on long-term follow-up after childhood-onset CP are focused on survival rates and lack information on specific sequelae (22,25,26,27,30). However, QoS is frequently impaired in the pediatric age group due to treatment and/or disease-associated factors such as HI, neuropsychological (31,32) and neuroendocrine deficits (16,21,33,34,35,36,37,38,39,40,41,42) including GH deficiency being the most frequent pituitary deficiency (54-100%) (1,37,39). Our study is the first report in the literature, which analyzed not only long-term survival but also psychosocial status and QoS with special regard to timing and duration of GH substitution therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, postoperative panhypopituitarism was mainly seen in patients who underwent GTR. Recently, in accordance with our findings, it has been demonstrated that conservative surgery may limit neuroendocrine sequelae . The relation between endocrine deficiencies and the development of obesity in childhood cancer survivors has been previously observed.…”
Section: Discussionmentioning
confidence: 99%
“…14 ESBS, however, has been shown to achieve higher rates of hypothalamic preservation regardless of the degree of involvement by tumor. 78,88 While TCSs for craniopharyngioma resection have been applied for many years, there are ongoing efforts to evaluate and improve these approaches to reduce the rates of significant morbidity. Minimally invasive modifications such as the supraorbital keyhole approach, with or without endoscopic assistance, have been used for lesions extending into the third ventricle and with significant retrochiasmatic components.…”
Section: Craniopharyngiomamentioning
confidence: 99%